2021
DOI: 10.5304/jafscd.2021.102.036
|View full text |Cite
|
Sign up to set email alerts
|

Food hubs play an essential role in the COVID-19 response in Hawai‘i

Abstract: Community food security and food systems resili­ence have received much emphasis in the last two decades, at least partially in response to mounting challenges and pressures on the global food system. While empirical research shows strong evidence that direct-to-consumer relationships in the food system predominantly serve affluent commu­nities, during the COVID-19 pandemic local food providers have become a necessity through their provision of essential services, such as hunger relief and home deliveries for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…It remains unclear to what extent this redundancy was useful or was too fragmented and overwhelming for business decision-makers. Fardkhales and Lincoln (2021) describe the value of redundancy in diverse systems when responding to a crisis such as the COVID-19 pandemic. Glaros et al (2021) further explain how supply networks, as opposed to chains, work toward community resilience.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear to what extent this redundancy was useful or was too fragmented and overwhelming for business decision-makers. Fardkhales and Lincoln (2021) describe the value of redundancy in diverse systems when responding to a crisis such as the COVID-19 pandemic. Glaros et al (2021) further explain how supply networks, as opposed to chains, work toward community resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Short food supply chains (SFSCs) 1 are becoming increasingly popular as a way for consumers to purchase local food, and many countries have implemented policies to facilitate their development (Kneafsey et al 2013 ; Rahe et al 2019 ; Fardkhales and Lincoln 2021 ). Since SFSCs involve few or no middlemen, participating farmers are often more autonomous and have a greater ability to set prices independently (European Commission 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hawaiʻi has been described as a model social-ecological system (Kirch 2007 ) and it has been suggested that indigenous agro-ecosystems have the potential to be highly productive and resilient under changing land-use and climate change disturbance (Kurashima et al 2019 ). However, little research has yet been conducted exploring the disruption and resilience of agro-ecosystems in Hawaiʻi caused by the COVID-19 pandemic (Fardkhales and Lincoln 2021 ; Lee and Milne 2020 ; Miles and Merrigan 2020 ; Worstell and Green 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hawaiʻi’s local food system is being tested by the crisis caused by COVID-19 which in March 2020 imposed stay-at-home orders, strict travel restrictions, and business closures, lasting more than a year (Fardkhales and Lincoln 2021 ). According to the Hawaiʻi Department of Agriculture, estimates in early summer of 2020 showed that local farmers and ranchers have seen a 50% decline in sales (Lee and Milne 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation